The supernatural in the theomachy of 2 Maccabees 9:1–29 and its role in the communicative strategy: A syntactical, semantic and pragmatic analysis - Coetzer, Eugene ca. 21. Jh. (HTS teologiese studies, 2018)
Throughout the prefixed letters and narrative of 2 Maccabees, a frequent overemphasis is discovered on certain concepts within every section or pericope. This is a logical product of such a highly rhetorical work, as this links to the overarching narrative aim of the text. These emphases subsequently lead to the question of their significance specific to this text and its subject matter. This article consequently notes, firstly, that 2 Maccabees deals with sensitive or innovative ideas and moves to drastic ways of conceptualising history in order to substantiate these ideas. It is no surprise, therefore, that in 2 Maccabees 9, one would find an overemphasis on the supernatural drive of world events to prove that the God of the Jews duly and appropriately deals with the enemies of his people. In order to explicate and unfold this process, the main ideas will be highlighted, communicative strategy investigated and the possible impact on the reader and/or hearer outlined.